Political rebellion causes, outcomes and alternatives - Gurr, Ted Robert 1936- (Routledge, 2015)
This volume comprises key essays by Ted Robert Gurr on the causes and consequences of organized political protest and rebellion, its outcomes and strategies for conflict management